SPECIFICITY OF THE DEVELOPMENT OF ACUTE CORONARY SYNDROME/ACUTE MYOCARDIAL INFARCTION IN MEN OF VARIOUS AGES IN ONE OF THE DISTRICTS OF TASHKENT (ACCORDING TO THE DATA OF REGISTRY) - O. U. Urinov (Евразийский Кардиологический Журнал)
To study specific features of the development and progressing of the acute coronary syndrome and acute myocardial infarction in men in different age groups in one of the districts of Tashkent.